Human(e) rights and the cosmopolitan imagination: questions of human dignity and cultural identity - Stevenson, Nick (SAGE Publications, 2014)
Here I seek to explore the cosmopolitan foundations of the idea of human rights. The argument begins by considering the popularity of the idea of human rights in a globalized and fast-moving commodified and digital culture. At this point I consider whether the idea of human rights might be considered to be a modern utopia similar to the role that art and nature played in the Romantic movements of the 19th century. Further, I defend human rights against those who simply see it as a form of neoliberalism or as largely ineffective against the power of the state. At this point I investigate some of the Durkheimian work within cultural sociology that has sought to investigate human rights as a form of moral community. The main problem with this view is that it has little to say about human freedom. However, viewed through a cultural lens, the global spread of human rights is connected to the idea of human dignity. While there is never likely to be a global consensus on this term, it does retain an important philosophical anchoring in Kantian ideas. More recently this debate has been revived by the critical reception of the work of Agamben and his idea of ‘bare life’. If human rights can indeed be connected to the struggle for a dignified and meaningful life, then the idea of ‘bare life’ remains an important conceptual advance. However, by considering the work and legacy of Du Bois, Gilroy and others, we can also see how the term dignity might take on other meanings in different settings. Finally, I argue that the idea of dignity and human rights could yet provide an important focus for resistance against the imperatives of capital and state in these neoliberal times.